Endothelial Function in Patients with Subclinical Hypothyroidism: A Meta-Analysis - Gong, Ningning; Gao, Cuixia; Chen, Xuedi; Fang, Yuan; Tian, Limin (Hormone and Metabolic Research, 2019)
The purpose of this meta-analysis was to determine whether patients with subclinical hypothyroidism (SCH) have impaired endothelial function, which is assessed by carotid intima-media thickness (C-IMT) and flow-mediated dilatation (FMD) of brachial artery. PubMed, Embase and Cochrane Library databases and the key studies references were searched in our study, prior to July 2017 for all language articles about FMD or C-IMT in SCH and euthyroid subjects. Two authors screened documents and extracted data by pre-established standard independently. The pooled estimate for continuous data was calculated using random-effects models. Statistical heterogeneity was evaluated using I2 statistics. Subgroup analyses were conducted to assess the robustness of the meta-analysis. Publication bias was examined with funnel plot analysis and Egger’s test. In this meta-analysis, 10 studies with 760 subjects are related to FMD with SCH and 23 studies with 1521 subjects are related to C-IMT with SCH. The pooled estimate of the weighted mean difference (WMD) has revealed that SCH correlated with increased C-IMT [WMD 0.069 mm; 95% CI (0.042, 0.095); p<0.001] and decreased FMD [WMD −1.848%; 95% CI (−2.298, −1.399); p<0.001] with high heterogeneity. Compared with EU controls, SCH was also associated with an increased diastolic blood pressure (DBP), systolic blood pressure (SBP), triglyceride (TG), total cholesterol (TC) levels, and low density lipoprotein cholesterol (LDL-C). This meta-analysis demonstrates that SCH is associated with endothelial dysfunction, which may relate with increased thyroid-stimulating hormone (TSH). Hypertension and dyslipidemia may play a crucial part in the development of endothelial dysfunction.
Keywords: endothelial function; subclinical hypothyroidism; meta-analysis